Encountering the Kura-Araxes. Changes in the Malatya plain at the end of the 4th millennium - Palumbi, Giulio; Frangipane, Marcella (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
The encounter of the communities of the Anatolian Upper Euphrates with the Kura-Araxes cultural traditions was a long and complex process that cannot be reduced to the abrupt ‘arrival’ of migrant communities from East Anatolia or South Caucasus. The historical, political and cultural ‘complexities’ embedded in this encounter are best exemplified by the case of Period VIB1 at Arslantepe, in the Malatya plain (Eastern Turkey). We examine at first the ‘structural’ and historical premises of this encounter by examining the Late Chalcolithic evidence from Arslantepe Period VIA witnessing the construction of a monumental palatial complex and the formation of a strong political élite. We believe that the political and economic changes witnessed in Period VIA also generated a sector of specialised herders that could have taken part to a wider sphere of interaction with other communities living in the wider mountainous areas of Central and North-Eastern Anatolia. In the second part of the paper, we examine more thoroughly Period VIB1, which followed the destruction of the palatial complex of Period VIA and that marks the earliest appearance of Kura-Araxes cultural traits in the Malatya region. Period VIB1 witnesses the temporary and reiterated occupations of specialized herders. Though a series of traits of continuity link cultural traditions and husbandry strategies of the Period VIB1 herders with those of Period VIA, the strong Kura-Araxes related ceramic repertoire of the Period VIB1 herders’signals a growing interaction with the regions of East Anatolia and South Caucasus. We suggest that the mobility of these herders could have fostered dynamics of cultural encounter and assimilation of the Kura-Araxes traditions. In the final section, we present new ceramic evidence from Period VIB1. The post-firing incised ceramics from Period VIB1 find close analogies with those from East Anatolia and South Caucasus in Phase Kura-Araxes I. Does not only this evidence confirm direct contacts with the eastern Kura-Araxes communities but the contexts of retrieval of these ceramics at Arslantepe add new suggestions on the ceremonial way in which the encounters between specialised herders from Arslantepe and the Kura-Araxes communities from East Anatolia and South Caucasus might have taken place.